Fundraiser for California Assemblyman race. - Sahl, Ted (photographer):::Creator::::::::::::
Paul Wysocki, center, a San Jose activists runs for city council. From left-to-right, Santa Cruz Councilman John Laird, Paul Wysocki and San Mateo County Supervisor Tom Nolan.